Pengaruh Media Video Animasi terhadap Pengetahuan Remaja tentang Covid-19 di Pesantren Al-husainiyyah (Jurnal Kesehatan Siliwangi, 2021)
This research is motivated by the high incidence of Covid-19 cases in Indonesia. WHO has declared the world has entered a global emergency related to the Covid-19 virus, data on March 15, 2021, the number of positive Covid-19 in Indonesia was recorded at 1,419,455 people, and 38,428 people died (Covid-19 Task Force, 2021). Sukabumi Regency there are 3,846 positive cases of Covid-19, and as many as 92 people have died. At the end of 2020 Sukabumi there was a transmission in the Pesantren cluster, as many as 286 students were infected with Covid-19. Incidents in school clusters need to be prevented considering that the Ministry of Education and Culture decided to reopen learning activities in July 2021. Therefore, providing education about Covid-19 needs to be carried out to prevent cluster cases in educational institutions from recurring. This study aims to determine the effect of animated videos on adolescent knowledge about COVID-19 at the Al-Husainiyah Islamic Boarding School, Sukabumi Regency. This type of research is quantitative with a pre-experimental research design with a one group pretest-posttest without control design. The population was 70 students and the sample was taken using a total sample and data collection using a questionnaire. The results showed that there was a difference in the average value before being given educational media was 80,54 and after being given educational media 94,83, then the data normality test was carried out using the One-Sample Kolmogorov- Smirnov The results obtained are 0.721 > 0.05 so that the data is normally distributed, then paired T-test is tested and the results are 0.000 < 0.05, then H 0 is rejected and Ha is accepted. So it can be concluded that there is an influence on adolescent knowledge before being given animated video media and after being given animated video media about Covid-19. Keywords: Knowledge, Media, Animated Video, Covid-19